KAJIAN KRITIS DAMPAK KEBIJAKAN IZIN USAHA RITEL (MINIMARKET) TERHADAP KEBERLANGSUNGAN PEMBANGUNAN EKONOMI KERAKYATAN - Agus Dimyati (Fakultas Hukum Universitas Swadaya Gunung Jati, 2014)
ABSTRACTThe growth of modern stores, especially minimarket type, recently has grown up not only in big cities but also in a town. Since the distance between traditional retail and the minimarket in in a same range of services, it will influence the community preferences in determining a place to shop. The purpose of this study is to investigate the characteristics of traditional retail and minimarket, public perception and preference towards them, and also to understand the effect of the minimarket existence to the traditional retail associated with a range of services. This study uses many method of research such as IPA, crosstab, modern retail’s impactsanalysis, and service coverage overlay. Each trading facilities, both traditional and modern retail has their advantages and disavantages based on the variables assessed by the consumer. There is a changes of trend in shopping destination selection preferences before and after the expansion of minimarket. District. Based on the rangeg of services, it is known that the greater service range of minimarket, it will effect to the much more traditional retail that is influence by the range of services. One of minimarket in the region Blimbing District has effected to the four traditional stores surrounding them, with an average of 57.29% friction. Based on the result from his research, when the traditional retail is near from minimarket, the biggest effect is on consumer whocome in every each day. Keyword: Impact, Traditional retail, Mnimarket, Range of service